Peru: ¿Educación bilingüe en un pais plurilingüe?. Sonia M. Steckbauer. Madrid: Iberoamericana; FrankfurtlMain: Vervuert, 2000, 195 pp. - Denisse M. Roca (Anthropologica, 2001)
El artículo no presenta resumen.